If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -1) = 3(x + 1) Reorder the terms: 6(-1 + x) = 3(x + 1) (-1 * 6 + x * 6) = 3(x + 1) (-6 + 6x) = 3(x + 1) Reorder the terms: -6 + 6x = 3(1 + x) -6 + 6x = (1 * 3 + x * 3) -6 + 6x = (3 + 3x) Solving -6 + 6x = 3 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -6 + 6x + -3x = 3 + 3x + -3x Combine like terms: 6x + -3x = 3x -6 + 3x = 3 + 3x + -3x Combine like terms: 3x + -3x = 0 -6 + 3x = 3 + 0 -6 + 3x = 3 Add '6' to each side of the equation. -6 + 6 + 3x = 3 + 6 Combine like terms: -6 + 6 = 0 0 + 3x = 3 + 6 3x = 3 + 6 Combine like terms: 3 + 6 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| 5xy(x+y)= | | (y-2)(y+4)=0 | | 6=2(7-c) | | y=16-6 | | 8-23x-14=9x-30x-6 | | 25-1.25x=16-.5x | | 15x-20=14x-21 | | 7+x(4)=16 | | -5n-8=16m | | 4x-5-6=12x-x-4-3x-7 | | 10n=9n+27 | | 24-8x=-2x+-10 | | x-(3x+7)=29 | | d-1=-9 | | 4x+(-4x)-2y+2y=-10+(-12) | | x+26-8x=8-4x | | 3x-6=60 | | q-e-(-2)=7-q | | 36=39 | | x^3-4x^2-11x+2=0 | | (2x+56)=(8x+8) | | 6x-18=30-2x | | w^2+6w+14=0 | | 2(x+8)=2x+16 | | 4.9x^2-93.3x-125=0 | | 4x^2-13x+12=-2x+12 | | -5-3p=-5(1-7p) | | 37-2x=7x+20 | | 5x+18=13x-82 | | (x+3)m=26 | | 3*(4x)+7*(5x)=2x+5 | | 6g+(-4+2g)=1-g |